2007
DOI: 10.1002/jbm.a.31544
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan/polyethylene glycol blend fibers and their properties for drug controlled release

Abstract: Fibers of chitosan and polyethylene glycol (PEG), with salicylic acid as model drug incorporated in different concentrations, were obtained by spinning their solution through a viscose-type spinneret into a coagulating bath containing aqueous tripolyphosphate and ethanol. Chemical, morphological, and mechanical properties characterization were carried out, as well as the studies of the factors that influence the drug releasing from chitosan/PEG fibers. These factors included the component ratio of chitosan and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
46
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 18 publications
6
46
0
Order By: Relevance
“…By virtue of chitin NFs' reinforcing effect, chitin NFs could significantly increase the Young's moduli and tensile strengths of acrylic resins, and decrease thermal expansion without losing transparency or flexibility. Moreover, chitin NFs have powerful biological activities and several applications were proposed in biomedical field [64][65][66][67][68]. For instance, they have anti-inflammatory actions via the suppression of NF-κB and MCP-1 activations and they suppress fibrosis in an acute ulcerative colitis mouse model, indicating that chitin NF is potentially a novel medicine or functional food for patients with inflammatory bowel disease [69,70].…”
Section: Discussionmentioning
confidence: 99%
“…By virtue of chitin NFs' reinforcing effect, chitin NFs could significantly increase the Young's moduli and tensile strengths of acrylic resins, and decrease thermal expansion without losing transparency or flexibility. Moreover, chitin NFs have powerful biological activities and several applications were proposed in biomedical field [64][65][66][67][68]. For instance, they have anti-inflammatory actions via the suppression of NF-κB and MCP-1 activations and they suppress fibrosis in an acute ulcerative colitis mouse model, indicating that chitin NF is potentially a novel medicine or functional food for patients with inflammatory bowel disease [69,70].…”
Section: Discussionmentioning
confidence: 99%
“…Sterilized PDA plates were prepared and a spherical ditch was made with a sterile borer in an aseptic area (30)(31)(32)(33)(34).…”
Section: In Vitro Antifungal Activitymentioning
confidence: 99%
“…Based on excellent gel forming property, numerous chitosan-based hydrogels have been developed. It is reported that a chitosan/PEG hydrogel performed well-controlled release of the model drug and showed potential for local delivery (19). The alginate-chitosan-PLGA gel successfully delivered an immunomodulating peptide to treat experimental autoimmune encephalomyelitis in a mouse model (20).…”
Section: Introductionmentioning
confidence: 99%